Pengenalan Dasar Artifical Intellengence di Era Digitalisasi di SMK Sampang - Elvin Nury Khirdany; Rokip Rokip; Fatimatuz Zahrah; Faisol Faisol (FKIP, Universitas Palangka Raya, 2024)
Technology in the era of revolution 4.0 is no longer a foreign object in society but has become something that almost all human activities involve technology. However, there is a problem, namely that many of the younger generation do not know about artificial intelligence. The lack of knowledge and examples of artificial intelligence applications can be an obstacle for the younger generation to start studying artificial intelligence from an early age. Therefore, training regarding artificial intelligence needs to be socialized to students at Vocational High School Sampang so that they understand the scope and application of artificial intelligence. The method used in this community service uses survey, lecture and discussion methods. It is hoped that this socialization will provide openness for teenage students to understand and utilize quality technology. This community service provides benefits both for service partners or participants and for service members, including: (1) increasing knowledge related to generation Z, namely technological developments with the presence of artificial intelligence; and (2) after attending the training, participants expressed a high level of satisfaction with the implementation